Effects of peripheral irisin infusion on the glucose uptake in high-fat-diet-induced obese rats - Sandal, Süleyman; Tekin, Suat; Erden, Yavuz; Çağlayan, Ahmet Burak; Özyalın, Fatma; Çiğremiş, Yılmaz; Çolak, Cemil (Wiley, 2018)
[Abstract Not Available]
WOS: 000453220100146
Keywords: Peripheral Irisin Infusion; Glucose Uptake; Induced Obese